The Hot Universe with XRISM and Athena. Issue Volume 14:Issue S342(2019) (May 2018) - Guainazzi, M.; Tashiro, M. S.
Abstract: X-ray spectroscopy is key to address the theme of "The Hot Universe", the still poorly understood astrophysical processes driving the cosmological evolution of the baryonic hot gas traceable through its electromagnetic radiation. Two future X-ray observatories: the JAXA- led XRISM (due to launch in the early 2020s), and the ESA Cosmic Vision L-class mission Athena (early 2030s) will provide breakthroughs in our understanding of how and when large-scale hot gas structures formed in the Universe, and in tracking their evolution from the formation epoch to the present day.